Adjuvant Therapy With Sodium Alendronate for the Treatment of Experimental Periodontitis in Rats. Issue 10 (1st October 2015) - De Almeida, Juliano; Ervolino, Edilson; Bonfietti, Luiz Henrique; Novaes, Vivian Cristina Noronha; Theodoro, Letícia Helena; Fernandes, Leandro Araujo; Martins, Thiago Marchi; Faleiros, Paula Lazilha; Garcia, Valdir Gouveia
Abstract : Background: This study assesses the effects of topical sodium alendronate (SA) as an adjuvant to the mechanical treatment of ligature‐induced periodontitis in rats. Methods: Ninety animals were subjected to the induction of periodontitis via the installation of a ligature around the mandibular left first molar. After 7 days, the ligature was removed, and the animals were distributed into the following groups: 1) NT group (n = 30), no treatment; 2) SRP group (n = 30), scaling and root planing (SRP) and local irrigation with physiologic saline solution; and 3) SRP/SA group (n = 30), SRP and local irrigation with SA (10 −5 M). Ten animals from each group were euthanized at 7, 15, and 30 days after treatment. Histologic and histometric analyses were performed in the furcation region. The percentage of bone in the furcation (PBF) was measured. Immunohistochemical analyses for detecting the receptor activator of nuclear factor‐κB ligand (RANKL), osteoprotegerin (OPG), tartrate‐resistant acid phosphatase (TRAP), and activated caspase‐3 were performed at the furcation region. Results: Compared with the other groups, the SRP/SA group showed less local inflammation and better tissue reparation during the entire experiment. There was more PBF in the SRP/SA group than in the other groups at days 7 and 15. Stronger OPG immunolabeling and weaker RANKL immunolabeling were observed in the SRP/SA group at 15 and 30 days. There were fewer TRAP‐positive cells in the SRP/SA group than in the NT group at all of the time points. There was no difference in the number of activated caspase‐3‐positive osteocytes among groups and time points. Conclusion: It can be concluded that topical use of SA as an adjuvant to SRP is effective in the treatment of experimental periodontitis.